The Mothers in Racine's Play From La Thebaide to Phedre - Burville, Victor (My University, 1962)
Why did Racine return so persistently to works in which mothers are so fundamentally important? Do these roles, spaced as they are from the beginning to the end of his major creative period, mark stages in the development of this great playwright’s turbulent life? What forces filled the vacuum left in his psycho by the lack of a mother? To find answers to such questions, we shall consider each of the mother-roles in its setting.
Keywords: Play; Mother